KING CONGO WAS FOR WAR, OH MY GOD HOW WILL IT BE? (Ágora Journal, 2020)
This article seeks to systematize some impressions obtained in research on slavery and popular culture in the central region of Espírito Santo. Two striking facts of local history will be revisited in an effort to identify a historical and narrative link between them. The first fact is the Insurrection of Queimado, a slave revolt that took place in one of the parishes of the provincial capital, Vitória, in 1849. And the second fact is a set of popular festivals and festivities originating in the black population that arose during the period of slavery and permanent to the present day in a cultural area covering a large part of Espírito Santo. For this purpose, the work will present, first, the revolt and unveil a little of the history of the region in which it took place, then aspects of the origin and description of the folkloric cycle of the congo bands.